THE AURIFEROUS SUBMARINE FANS SANDSTONES OF THE IONIAN ZONE (EPIRUS, GREECE) - Manoutsoglou, E.; Batsalas, A.; Stamboliadis, E.; Pantelaki, O.; Vakalas, I.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2010)
During recent decades many studies have be done on the rocks that developed in the area of Western Greece and especially in Epirus, known in geoscientific literature as Ionian Zone of External Hellenides. These rocks have undergone geological research (basic geological mapping, research for hydrocarbons, metals and inert materials) and exploitation (inert materials). Recently, within the sedimentary succession of the Ionian zone submarine fans, in the region of Peta–Kompoti, in the prefecture of Arta, have been identified positions where sedimentary gold is present. Recently, positions where sedimentary gold is present, within the sedimentary rocks of the submarine fans, in the region of Peta–Kompoti, prefecture of Arta, have been identified. For the continuation and the practical application of these positive results, it was necessary to obtain a documented reference of geological parameters. After a series of new sampling and detailed analysis of the samples, this work presents the detected gold concentrations, illustrates the limits of grouping areas of interest as well as delineating and illustrating palaeogeographic factors that have contributed to the creation of gold-bearing formations. The highest gold concentration found was in the Ta Bouma sequence. The observation of constant indications of high gold values above background that suddenly increase in certain places up to 260 ppb, leads to the conclusion that in the broader area and within locations with equivalent formations procedure, there could be gold pockets of exploitable concentrations.